Efektivitas Ekstrak Kulit Rambutan (Nephelium lappaceum L.) pada Kadar Kreatinin dan Struktur Histologi Ginjal Tikus Obesitas - Shalsabila, Fitria; Lisdiana, Lisdiana (Journal of Pharmaceutical and Sciences, 2025)
Obesity is a condition characterized by the accumulation of excess fat in the body that can cause systemic metabolic changes. Rambutan peel is known to be rich in bioactive compounds such as geraniin, corilagin, ellagic acid, and other active compounds. This study aims to analyze the effect of rambutan peel extract on creatinine levels and kidney histology in obese rat models. The experimental research method used a post-test only control group design. A total of 25 male rats were divided into 5 groups: Normal group (K-); Obese group induced by coconut oil and 15% sugar water (K+); Obese group given ellagic acid (T1); Groups T2 and T3 induced by coconut oil and 15% sugar water and rambutan peel extract at doses of 15 mg/kgBW and 30 mg/kgBW. The parameters of this study were creatinine levels and kidney glomerular diameter. Data analysis used one-way ANOVA and Tukey HSD tests. The results of the study showed that rambutan peel extract could significantly reduce creatinine levels and glomerular diameter (p<0.05). The most optimal reduction was shown at a dose of 30 mg/kgBW for both creatinine levels and glomerular diameter. It can be concluded that rambutan peel extract has the potential to reduce creatinine levels and improve glomerular diameter in obese rat models.